Development of high intensity ultrasonic (HIU) for in-situ stainless steel filter leaf cleaning - Rosli Mohd. Yunus; Radzuan Junin; Ahmad Ziad Sulaiman; Hasrinah Abdullah; Regional Symposium of Membrane Science and Technology (2002 : Songkla, Thailand) (Skudai : Universiti Teknologi Malaysia, 2002)
40